Dengue Virus Infection of Primary Human Smooth Muscle Cells - Arias Arias, Jorge Luis (2018)
Dengue virus (DENV) infection of humans is presently the most important arthropod-borne viral global threat, for which no suitable or reliable animal model exists. Reports addressing the effect of DENV on vascular components other than endothelial cells are lacking. Dengue virus infection of vascular smooth muscle cells, which play a physiological compensatory response to hypotension in arteries and arterioles, has not been characterized, thus precluding our understanding of the role of these vascular components in dengue pathogenesis. Therefore, we studied the permissiveness of primary human umbilical artery smooth muscle cells (HUASMC) to DENV 1-4 infection and compared with the infection in the previously reported primary human umbilical vein endothelial cells (HUVEC) and the classically used, non-transformed, and highly permissive Lilly Laboratories Cell-Monkey Kidney 2 cells. Our results show that HUASMC are susceptible and productive to infection with the four DENV serotypes, although to a lesser extent when compared with the other cell lines. This is the first report of DENV permissiveness in human smooth muscle cells, which might represent an unexplored pathophysiological contributor to the vascular collapse observed in severe human dengue infection.